Pluripotent Stem Cells for the Treatment of Retinal Degeneration: Current Strategies and Future Directions - Ikelle, Larissa; Al-Ubaidi, Muayyad R.; Naash, Muna I. (Frontiers in Cell and Developmental Biology, 2020)
Stem cells have been part of the biomedical landscape since the early 1960s. However, the translation of stem cells to effective therapeutics have met significant challenges, especially for retinal diseases. The retina is a delicate and complex architecture of interconnected cells that are steadfastly interdependent. Degenerative mechanism caused by acquired or inherited diseases disrupt this interconnectivity, devastating the retina and causing severe vision loss in many patients. Consequently, retinal differentiation of exogenous and endogenous stem cells is currently being explored as replacement therapies in the debilitating diseases. In this review, we will examine the mechanisms involved in exogenous stem cells differentiation and the challenges of effective integration to the host retina. Furthermore, we will explore the current advancements in trans-differentiation of endogenous stem cells, primarily Müller glia.